Determinasi Faktor-Faktor yang Mempengaruhi Nilai Perusahaan - Deby Ilma Aulia; Setiawati, Erma (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to identify the factors affecting firm value in food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period of 2021-2023. The research is quantitative, using statistical analysis and secondary data derived from financial statements. The dependent variable is firm value, measured using Price to Book Value (PBV), while the independent variables include investment decisions (Price Earnings Ratio/PER), financing decisions (Debt to Equity Ratio/DER), dividend policy (Dividend Payout Ratio/DPR), and profitability (Return on Equity/ROE). The analysis method employed is multiple linear regression, preceded by classical assumption testing. The results reveal that investment decisions and profitability have a positive effect on firm value, while financing decisions and dividend policy do not significantly affect firm value. The study is limited by a small sample size and a short research period.